Visual–tactile processing in primary somatosensory cortex emerges before cross‐modal experience. Issue 6 (21st February 2017) - Bieler, Malte; Sieben, Kay; Schildt, Sandra; Röder, Brigitte; Hanganu‐Opatz, Ileana L.
Abstract: The presumptive unisensory neocortical areas process multisensory information by oscillatory entrainment of neuronal networks via direct cortico‐cortical projections. While neonatal unimodal experience has been identified as necessary for setting up the neuronal networks of multisensory processing, it is still unclear whether early cross‐modal experience equally controls the ontogeny of multisensory processing. Here, we assess the development of visual–somatosensory interactions and their anatomical substrate by performing extracellular recordings of network activity in primary sensory cortices in vivo and assessing the cortico‐cortical connectivity in pigmented rats. Similar to adult animals, juvenile rats with minimal cross‐modal experience display supra‐additive augmentation of evoked responses, time‐dependent modulation of power and phase reset of network oscillations in response to cross‐modal light and whisker stimulation. Moreover, the neuronal discharge of individual neurons is stronger coupled to theta and alpha network oscillations after visual–tactile stimuli. The adult‐like multisensory processing of juvenile rats relies on abundant direct visual–somatosensory connections and thalamocortical feedforward interactions. Thus, cellular and network interactions ensuring multisensory processing emerge before cross‐modal experience and refine during juvenile development. Abstract : Combining extracellular recordings in vivo and anatomical investigations in pre‐juvenile rats, the authors show that the processing of visual–tactile information and the underlying direct connectivity between the primary sensory cortices emerge before and to a large extent independently of cross‐modal experience.